Penyuluhan tentang Pencegahan dan Penanganan K3 di UMKM Azka Sala Lauak RW 02 Meranti Pandak - Juniar Ernawaty; Aulia Rahma Dinda; Dela Melani; Rahayu Annisa Fitri; Rana Roidah Trianti; Saltsabillah Muzaidan (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Work accidents are incidents in the workplace that can cause injury, work-related illnesses, or death. Work accidents can occur in every sector, one of which is in the UMKM (Micro, Small and Medium Enterprises) industry. One of the UMKMs in RW 02 Meranti Pandak is Azka Sala Lauak, which is included in the fried food business. Work accidents that can occur in this business are burns due to hot oil splashes, slipping due to slippery floors and gas explosions. This activity aims to increase workers' knowledge regarding the prevention and handling of work accidents in UMKM Sala Lauak. The method used in this counseling is lectures. From the results of the counseling, it was found that workers' knowledge increased about the prevention and handling of work accidents in UMKM Sala Lauak from 9.80 to 13.07. It can be concluded that the counseling carried out was effective because there was an increase in participants' knowledge about the prevention and handling of work accidents in UMKM Sala Lauak.